Relationship with Nut Consumption for Breakfast and Postprandial Glucose, Insulin, Triglyceride Responses: A Preliminary Study from Türkiye - Ipek Agaca Ozger; Gizem Kose; Murat Bas; Sena Oruc; Ladan Hajhamidiasl; Salim Yilmaz (Foods, 2024)
This study aimed to determine the effect of adding nuts to a regular breakfast on blood glucose, insulin, and triglyceride levels, and to evaluate participants’ opinions by sex as a preliminary study for future studies. Data and biochemical parameters were collected through face-to-face interviews with Acibadem Hospital employees (n = 12) between April and September 2023. Participants consumed 30 g of nut-supplemented breakfasts for 4 weeks while maintaining their regular lifestyle. Blood tests and visual analog scale (VAS) parameters were assessed on intervention days. VAS scores indicated differences in meal taste, post-breakfast well-being, satiety, and meal adequacy, and for “feeling better after breakfast”, and “providing better satiety”, were significantly higher for the nut-supplemented breakfasts (p < 0.05), especially walnut-supplemented. Under the control of age, sex, and BMI variables in the participants, women responded better to peanut butter consumption than men in terms of blood insulin and triglyceride regulation (p < 0.05). However, triglyceride regulation in men was better managed by walnut consumption than in women. Understanding how nut-supplemented breakfasts impact blood glucose, insulin, and triglyceride levels, as well as consumer perceptions, is crucial for promoting healthier dietary choices.